PENGAKHIRAN PERJANJIAN SEPIHAK DALAM PERSPEKTIF HUKUM DAN HAK ASAS MANUSIA - Yanuar Fajri (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
Human rights are inherent in every human being to have the same rights, including unilateral termination of agreements, then human rights are disturbed and not protected. The research method uses normative juridical research, namely the doctrinal method, namely taking an inventory of positive law, discovering legal principles and doctrines, synchronizing existing laws and regulations and conducting research by examining and examining various existing literature. With a Legislative Approach, Historical Approach, Comparative Approach, and Conceptual Approach. The research results show that terminating a unilateral agreement can potentially be categorized as an unlawful act if the unilateral termination of the agreement is carried out without a valid reason, violates the principles of propriety and the law, causing harm to the other party. In addition, unilateral termination of an agreement if carried out without a valid reason violates human rights related to the right to guarantee legal certainty and human freedom without discrimination.